Developing tasks to assess phenomenon‐based science learning: Challenges and lessons learned from building proximal transfer tasks. Issue 6 (6th August 2019) - Penuel, William R.; Turner, Michael L.; Jacobs, Jennifer K.; Van Horne, Katie; Sumner, Tamara
Abstract: The vision for science proficiency presented in A Framework for K‐12 Science Education calls for significant shifts in both teaching and assessment. In this paper, we describe an effort to develop and validate a set of proximal transfer tasks for high school biology classrooms where teachers were implementing a problem‐based curriculum. The proximal transfer tasks presented students with phenomena related to but distinct from the phenomena they had studied in class and asked students to apply their understanding of disciplinary core ideas, practices, and crosscutting concepts targeted in curriculum. We tested these tasks with a sample of 733 students from 11 teachers' classes. Each of these students completed two tasks before beginning the unit and two tasks after they had finished the unit. We found that nearly all pretest and posttest task pairs were aligned to written opportunities to learn in the curriculum, that is, students showed significant growth over the course of a unit. In addition, task pairs revealed differences across teachers. However, the relative growth of students depended on which tasks students completed, indicating wide variation in task difficulty. Our findings point to the potential of developing three‐dimensional proximal transfer tasks and to the difficulty of constructing equivalent tasks.